2012
DOI: 10.1016/j.mambio.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Winter site occupancy patterns of the northern flying squirrel in boreal mixed-wood forests

Abstract: a b s t r a c tWe assessed habitat use by the northern flying squirrel (Glaucomys sabrinus) to test the hypothesis that the species is not a late-seral coniferous forest specialist in boreal mixedwood forests of northwestern Québec. We monitored 149 pairs of nest boxes over 3 visits during February-April 2008. A total of 31 pairs of nest boxes were occupied during the study. The average (3.7, 2.8, and 1.8) and maximum (8, 6, and 4) numbers of individuals in nest boxes decreased from the first to last visit. Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our patterns of overall mean abundance of G. sabrinus reached this level in various stand conditions. Smith (2007), Trudeau et al (2012), andPriol et al (2014) suggested that G. sabrinus may be more of a generalist species occupying a broader array of forest habitats than earlier postulated.…”
Section: Glaucomys Sabrinusmentioning
confidence: 87%
“…Our patterns of overall mean abundance of G. sabrinus reached this level in various stand conditions. Smith (2007), Trudeau et al (2012), andPriol et al (2014) suggested that G. sabrinus may be more of a generalist species occupying a broader array of forest habitats than earlier postulated.…”
Section: Glaucomys Sabrinusmentioning
confidence: 87%
“…The use of nest boxes as roosting sites by red squirrels (Tamiasciurus hudsonicus Erxleben) and northern flying squirrels (Glaucomys sabrinus Shaw) is also common [69,70]. However, given their ability to construct bolus nests in the tree canopy and use underground burrows [71], squirrels are likely not limited by cavity availability [72].…”
Section: Effect Of Cavity Supplymentioning
confidence: 99%